Is There a Future for Remote Cardiac Implantable Electronic Device Management? - Burri, Haran (Arrhythm Electrophysiol Rev, 2017)
In the era of communication technology, remote monitoring has been a paradigm shift in the way patients with cardiac implantable electronic devices are managed. It has been endorsed by scientific societies and is being increasingly adopted in the clinical setting. Despite the various advantages associated with this strategy, data on improved clinical outcome are still sparse. The recently published study on the remote management of heart failure using implanted devices and formalised follow-up procedures, which turned out to be negative, has cast doubt on whether remote monitoring should still be used. This article provides a critical appraisal of the study, and discusses the issue of remote data management.